Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.2196/preprints.36086
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Research on Digital Technology Use in Cardiology: Bibliometric Analysis (Preprint)

Abstract: BACKGROUND Digital technology uses in cardiology have become a popular research focus in recent years. However, there has been no published bibliometric report that analyzed the corresponding academic literature in order to derive key publishing trends and characteristics of this scientific area. OBJECTIVE We used a bibliometric approach to identify and analyze the academic literature on digita… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 111 publications
1
1
0
Order By: Relevance
“…Of these, the United States made the largest contribution to this field, accounting for over 50% of the studies. Previous bibliometric research related to cardiac diseases also showed similar results, with the United States emerging as the most prolific country in research quantity (34,35).…”
Section: Authorship and Country Collaborationssupporting
confidence: 63%
See 1 more Smart Citation
“…Of these, the United States made the largest contribution to this field, accounting for over 50% of the studies. Previous bibliometric research related to cardiac diseases also showed similar results, with the United States emerging as the most prolific country in research quantity (34,35).…”
Section: Authorship and Country Collaborationssupporting
confidence: 63%
“…We included the three most popular published databases: PubMed, Web of Science, and Scopus. Therefore, our results are more inclusive as compared to prior studies, which focused on only one of the aforementioned databases (34,35,46). To our knowledge, this is the first study to provide a comprehensive picture of the HL tools used in observational and interventional studies related to heart diseases.…”
Section: Health Literacy Questionnairesmentioning
confidence: 93%